2-Bromo-3-hydroxy-6-methylpyridine - Singh, Govind Pratap (International Union of Crystallography, 2013)
In the title compound, C(6)H(6)BrNO, the Br atom is displaced from the pyridine ring mean plane by 0.0948 (3) Å, while the hydroxyl O atom and the methyl C atom are displaced by 0.0173 (19) and 0.015 (3) Å, respectively. In the crystal, molecules are linked via O—H⋯N hydrogen bonds, forming chains propagating along the a-axis direction. These chains are linked by C—H⋯Br hydrogen bonds, forming corrugated two-dimensional networks lying parallel to the ac plane.